Visible-Light Mediated Synthesis of Nitrogen and Sulfur Containing Compounds: A Greener Approach - Kamal, Arsala (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Visible-Light Mediated Synthesis of Nitrogen; Sulfur Containing Compounds; A Greener Approach